Acaricidal activity and repellency of Blechnum cordatum (Blechnaceae) against Tetranychus urticae (Acari: Tetranychidae). (2019)
Tetranychus urticae is a highly polyphagous mite species, with 1,140 host plant species reported worldwide. In this study, both Blechnum cordatum toxicity and repellent activity against T. urticae are reported. Regarding toxicity, the ethyl acetate fraction at 250 ppm and the n-hexane fractions at 250 ppm and 100 ppm caused the greatest accumulated mortality rate when application was made starting during the larval stage. Results showed that even at the lowest evaluated concentration (10 ppm), both fractions caused a significant decrease in the T. urticae population. The n-hexane fraction caused 100 % repellency at 50 ppm and repellency significantly superior to the control at 10 ppm. Relatively low activity was found when treatments were applied directly to adults. In addition, results suggest that the cumulative mortality could have been caused by starvation due to the observed repellency and the well-known deterrent activity of phytoecdysteroids (PEs) found in the extracts. Four PEs from the B. cordatum n-hexane fraction were isolated: ecdysone, ponasterone A, shidasterone and 2-deoxycrustecdysone.